Surgical-Site Infection Prevention After Hysterectomy: Use of a Consensus Bundle to Guide Improvement. Issue 4 (July 2020) - Burgess, Adriane; Fish, Megan; Goldberg, Seth; Summers, Keziah; Cornwell, Kim; Lowe, Jason
Abstract : ABSTRACT: Hysterectomy is one of the most commonly performed surgeries in women. Surgical-site infections (SSI) after hysterectomy can lead to increased morbidity and mortality as well as readmission, which is associated with increased costs for health systems. The aim of the project was to improve standardization of preoperative education on infection prevention and incorporate the use of preoperative chlorhexidine (CHG) bathing for patients undergoing hysterectomy to decrease rates of SSI. Data on SSI after hysterectomy were reviewed. Tracer methodology was used to identify gaps in the preoperative process by comparing the current process to the Council on Patient Safety in Women's Health Care Patient Safety Bundle " Prevention of Surgical Site Infection after Gynecologic Surgery ." After implementation, survey data were collected on adherence to the washing protocol, and SSI data were monitored. Survey results reflected high compliance with the CHG washing protocol, provision of patient education, and overall patient satisfaction with the process. Before implementation in 2016, we reported 8 deep or organ/space SSI to the National Healthcare Safety Network. After implementation in 2018, we reported 3 deep or organ/space SSI. Standardizing infection prevention processes to align with safety bundles improves the quality of care provided to patients. Abstract : Supplemental Digital Content is Available in the Text.